2009
DOI: 10.1021/jp810256x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Spectroscopic Studies of the Photophysical Properties of Benzophenone Derivatives

Abstract: The effect a solvent has on the photophysical properties of a series of benzophenone derivatives, all FDA approved for use in sunscreens, is examined. Experimentally significant differences in the solvatochromic behavior are found to be dependent upon the substituents on the parent benzophenone molecule. The spectral trends do not appear to originate from only changes in the solvent polarity but indicate that specific solvent-solute interactions influence the absorbance energies of some benzophenones. Computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…In this study, both were determined using an indirect method consisting of the comparison between the amount of BZ- encapsulated in lipid nanoparticles, and the total amount of the colloidal system, in accordance with equations 1 and 2. The BZ-3 is an active desirable as sunscreen exhibiting a protection factor (SPF) greater than 15, due to their strong absorption in the regions of UVA (320-400 nm) and UVB (290 -320 nm) [21].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, both were determined using an indirect method consisting of the comparison between the amount of BZ- encapsulated in lipid nanoparticles, and the total amount of the colloidal system, in accordance with equations 1 and 2. The BZ-3 is an active desirable as sunscreen exhibiting a protection factor (SPF) greater than 15, due to their strong absorption in the regions of UVA (320-400 nm) and UVB (290 -320 nm) [21].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of a solvent on the absorption spectrum of a solute is an essential study for the development of solution chemistry [6][7][8][9][10][11]. When absorption spectra are measured in solvents of different properties, it is found that the positions, intensities, and shape of absorption bands are usually influenced by the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The phototoxic skin reactions by KT, MX, and OX have been reported on the basis of the results from human photopatch tests (Chuah et al, 2013;Infante Hernando et al, 2013), although these are directly applied to the skin. OX, SB, DO, and MX were developed as sunscreens (Darvay et al, 2001;Baughman et al, 2009), and KT is one of the most well known nonsteroidal anti-inflammatory drugs given via the dermal route. In this investigation, UV spectral analysis and ROS assay were carried out to evaluate the photochemical properties of BZPs, and 3T3 NRU PT was also undertaken to verify the in vitro phototoxicity of BZPs.…”
Section: Introductionmentioning
confidence: 99%